Mathematical problems and puzzles from the Polish mathematical olympiads - Straszewicz, S. (Stefan) (Popular lectures in mathematics (New York, N.Y.) ;, 1965)
Popular Lectures in Mathematics, Volume 12: Mathematical Problems and Puzzles: From the Polish Mathematical Olympiads contains sample problems from various fields of mathematics, including arithmetic, algebra, geometry, and trigonometry. The contest for secondary school pupils known as the Mathematical Olympiad has been held in Poland every year since 1949/50.